ASSESSMENT OF SHELFLIFE DURING ICE STORAGE OF THREE COMMERCIALLY IMPORTANT SMALL INDIGENOUS FISH SPECIES OF NORTHEAST INDIA - Majumdar, R. K.; Nath, Kapil Deb (Journal of Indian Fisheries Association, 2013)
Shelf-life of Mystus gulio, Puntius sophore and Gudusia chapra during ice storage was studied through evaluation of biochemical, microbial and organoleptic changes. Proximate analysis of those three fishes revealed the moisture, ash, protein and lipid contents which were 74.76, 1.58, 16.87 and 5.69 for Mystus gulio, 72.55, 1.72, 18.21 and 4.49 for Puntius sophore and 73.18, 1.77, 16.24 and 4.43 for Gudusia chapra. The TVBN increased to 29.87 mg% on 10th day in Puntius sophore, whereas, it crossed the border line of spoilage on 13th day in Mystus gulio and Gudusia chapra. The aerobic plate count reached to an average of 6 log cfu g-1 on day 13th for Mystus gulio and Gudusia chapra and day 10th for Puntius sophore. The results indicated that the edible quality of Mystus gulio and Gudusia chapra was maintained up to 13 days and Puntius sophore up to 10 days when stored with ice.Â Keywords: Mystus gulio, Puntius sophore, Gudusia chapra, ice storage, biochemical changes, shelf life. Â